Strategi Pembelajaran Dalam Konsep Al-Zarnuji - Akhmad khoiri (Sekolah Tinggi Ilmu Tarbiyah Darul Fattah, 2022)
Education is a social human process that can cause a person to submit to obeying religion, nation to be applied perfectly in the lives of individuals and society. A teacher is someone who transfers knowledge to learners. A student is a person who is studying science. In education requires a learning strategy to get the desired goal. This research article is qualitative research using the descriptive method. The method that will be used in this research is library research. This article discusses learning strategies in the concept of Al-Zarnuji in the book of Ta'lim al-Mutaalim contains 4 learning strategies contained in the façade of the façade compiled by Al-Zarnuji. This strategy is still very relevant to be applied to this cook to improve the quality of education from the aspect of morality without ruling out the intellectual aspect. Keywords: Teacher, Student, Al-Zarnuji, Learning Strategy, Ta'lim al-Muta'allim.